Serum-derived bovine immunoglobulin for children with diarrhea-predominant irritable bowel syndrome - Arrouk R; Herdes RE; Karpinski AC; Hyman PE (Dove Medical Press, 2018)
Rami Arrouk,1 Rachel E Herdes,1 Aryn C Karpinski,2 Paul E Hyman1 1Department of Pediatrics, Louisiana State University, New Orleans, LA 70118, USA; 2Evaluation and Measurement Program, School of Foundations, Leadership, and Administration, College of Education, Health, and Human Services, Kent State University, Kent, OH 44240, USA Background: Oral serum-derived bovine immunoglobulin (SBI)/protein isolate is a medical food intended to manage chronic diarrhea. It has been shown to improve pain and diarrhea in adults with diarrhea-predominant irritable bowel syndrome (d-IBS). Aim: To determine if SBI can improve symptoms in children with d-IBS. Methods: We performed a randomized, double-blind, placebo-controlled, pilot study (NCT02609529) to evaluate the effectiveness of SBI in children 8–18 years with d-IBS. We recorded stool number, abdominal pain, and stool form in all patients for 1 week and then assigned the patients at a ratio of 2:1 to treatment with SBI 5 g BID or placebo for 3 weeks. The patients and their parents completed the Pediatric Quality of Life Inventory™ for Gastrointestinal Symptoms (PedsQOL) and the Pediatric Functional Disability Index (FDI). In addition, complete blood counts and serum chemistries were recorded at the start and end of treatment to evaluate safety. Results: Fifteen patients (nine SBI, six placebo) completed the study. Both SBI and placebo groups reported nonstatistical reductions in stool frequency per week. The SBI group showed a significant reduction in stool frequency at weeks 1 and 2 but not at the end of treatment. The SBI group also demonstrated statistical improvements in abdominal pain and stool form by 3 weeks. The placebo group did not achieve similar improvements. The overall FDI and PedsQOL scores, as well as PedsQOL subscale scores for pain, discomfort when eating, diarrhea, worry about stomach aches, and communication, improved significantly in the SBI group, but not in the placebo group. No serious adverse events occurred. Serum chemistries and hemograms were normal at baseline and at the end of study in all patients. Conclusion: In this single-center, exploratory pilot study, we demonstrated that 10 g SBI per day was safe in children with d-IBS and improved symptoms. Larger studies, with longer treatment duration, seem warranted based on these initial positive results. Keywords: pediatric, irritable bowel syndrome, diarrhea, abdominal pain